Development of a Practical Life Busy Book Learning Medium for Teaching Hand–Eye Coordination at Nurul Ulum Preschool in Malang - Habibatul Azizah; Ayu Asmah; Cicilia Ika Rahayu Nita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Hand–eye coordination is essential for children's development. However, the development of hand–eye coordination among children aged 4–5 years has not yet reached its optimal level, indicating the need for effective learning media to support its development. This study aimed to determine the feasibility and practicality of developing a practical life busy book as a learning medium. The research employed both qualitative and quantitative methods. Data were collected at Nurul Ulum Playgroup, Tajinan, Malang, involving children aged 4–5 years through small-group trials (3 children), medium-group trials (7 children), and large-group trials (12 children). The study adopted the ADDIE research model, which consists of five stages. The findings showed that the material expert validation achieved a score of 93%, while the media expert validation reached 96%, both categorized as highly valid. The trial results obtained percentages of 73% in the small-scale trial, 84% in the medium-scale trial, and 94.5% in the large-scale trial, indicating that this learning medium is highly feasible for use with children aged 4–5 years. It can be concluded that the practical life busy book is practical and feasible for use in learning activities aimed at improving hand–eye coordination among children aged 4–5 years. The practical life busy book is expected to become an effective learning medium for enhancing the development of hand–eye coordination in children aged 4–5 years.